FEM study of elliptical coreoptical fibres - Mudzingwa, Courage; Nechibvute, Action (2016)
Elliptical core optical fibres have the distinct property of geometry birefringence which enables them to exhibit polarization maintaining characteristics. These specialty fibres are typically used to guide linearly polarised light from point to point thereby finding many specialised applications in optical sensors as well as telecommunications and sensor research.The 2D-FEM modal analysis presented in this paper relies on solving Maxwell’s equations of electromagnetic wave propagation using COMSOLMultiphysics®.The model developed in this study is adapted for FEM study of any elliptical core waveguide based on its geometry and doping concentration. The implementation of the FEM method in COMSOL enhances an insight into the numerical methodology and analyses factors that affect its performance. As a result, computational stability,convergence rate, modelling accuracy together with the influence of time and space step lengths can all be examined. Keywords – elliptical core optical fibre, specialty fibre, birefringence, 2D-FEM, propagation mode